Phytochemical Study of Euphorbia turcomanica Boiss. - Newsha Motinia; Mustafa Ghannadian; Behzad Zolfaghari; Zeinab Yazdiniapour (Metabolites, 2022)
The attraction to the Euphorbia genus, with its remarkable diversity in species, is due to its variety of chemical compositions. Euphorbia turcomanica is one of the species of the spurge family growing wildly in Iran. This research aims to investigate the presence of secondary metabolites, specially terpenoid compounds, in terms of structural determination. Samples of E. tucomanica were finely powdered and macerated with acetone/dichloromethane 2:1. Repeated column chromatography using silica gel, MPLC, and HPLC methods followed by the analysis of data obtained from spectroscopic means was carried out to purify and identify the terpenoid constituents. The chemical structures of nine known terpenoids were determined for the first time from E. turcomanica during this study. Loliolide (1), a monoterpene, and eight steroids and triterpenes, including simiarenol (2), isomultiflorenol (3), cycloart-25-ene-3β,24-diol (4), β-sitosterol (5), cycloart-23-ene-3β,25-diol (6), 3α, 11α-dihydroxyurs-12-ene (7), 3β, 24β, 25-trihydroxycycloartane (8), and 7α-hydroxystigmasterol (9) were isolated and identified. E. tucomanica, with a rich terpenoid profile, can be one of the valuable and economic sources providing compounds for drug development.